2008
DOI: 10.1007/s00270-008-9386-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment in Iliac Artery Occlusion: Long-Term Results

Abstract: We evaluated the long-term results of recanalization with primary stenting for patients with long and complex iliac artery occlusions. This was a retrospective nonrandomised study. Between 1995 and 1999, 138 patients underwent recanalization of an occluded iliac artery with subsequent stenting. Patency results were calculated using Kaplan-Meier analysis. The mean length of follow-up was 108 months. Variables affecting primary stent patency such as patient age; stent type and diameter; lesion site, shape, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 18 publications
3
44
0
Order By: Relevance
“…Recent series of primary stent placement for CTOs reported the 2-year primary and secondary or assisted primary patency rates of 69%-93% and 85%-95%, respectively. [3][4][5][6][7][8][9][10][11][12] Our series demonstrated 2-year primary and assisted primary patency rates of 91% and 96%, at the high end of the range of recent reports. However, although our patency rates for primary stents placed for iliac CTOs were better than those reported for extra-anatomic bypasses, such as axillofemoral and femorofemoral bypasses, these patency rates were not better than the patency conventionally reported for aortobifemoral bypass.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Recent series of primary stent placement for CTOs reported the 2-year primary and secondary or assisted primary patency rates of 69%-93% and 85%-95%, respectively. [3][4][5][6][7][8][9][10][11][12] Our series demonstrated 2-year primary and assisted primary patency rates of 91% and 96%, at the high end of the range of recent reports. However, although our patency rates for primary stents placed for iliac CTOs were better than those reported for extra-anatomic bypasses, such as axillofemoral and femorofemoral bypasses, these patency rates were not better than the patency conventionally reported for aortobifemoral bypass.…”
Section: Discussionsupporting
confidence: 48%
“…Our technical success rate was 100%, which was similar to that in most previous reports (97%-99%). 11,12 However, most investigators report technical problems that occurred with guidewire traversal of CTOs; guidewire crossing of these extensive lesions is rendered very diffi cult by the long fi brous cap and heavy calcifi cations that are invariably present. 1,2 A retrograde, ipsilateral approach may be preferable in most cases, since the tip of the guidewire can often be forced through the necrotic core of the lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3-year primary patency rates in PTA group alone were less than 60% [31,32] ; while primary patency rates in PTA plus stenting group reached up to 90% [33][34][35]. Bosch and colleagues [36] found that the technical success rate of iliac angioplasty plus stenting was higher than that in PTA group alone but without statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%